Outcome of Open Reduction and Internal Fixation with Interlocking Intra-Medullary Nail in the Treatment of Fracture of Shaft of Femur without Fluoroscopy - Sah, Shambhu; Yadav, Ram Kumar; Shrivastav, Shilabant Sen; Jha, Subash Chandra; Kharel, Yagya Raj; Karn, Navin Kumar; Karn, Shivam; Jha, Praveen (Birat Journal of Health Sciences, 2023)
Introduction: Femoral shaft fractures are among the common fractures generally managed by close reduction and internal fixation (CRIF) with interlocking intramedullary nailing (ILIMN) as the nail provides the rotational as well as longitudinal stability along with good clinical and functional outcomes but requiring fluoroscopy guidance. Also, in delayed cases, the close reduction might not be possible intimidating the need of open reduction.Objective: To assess the clinical outcome of the treatment from Open Reduction and Internal Fixation (ORIF) technique as well as placement tricks of locking screws in the absence of a traction table and fluoroscopy.Methodology: Fourteen cases of close femur fractures with transverse and oblique type in the middle 1/3 shaft coming to Koshi Hospital, Nepal, from June 2019 to December 2021 were included in this study. All patients were treated with ORIF with ILIMN technique without the use of a traction table and fluoroscopy.  Data collection included demography, mechanism of injury, mobilization time, union rate, infection, and complication. The study was also designed to evaluate the method of our technique which could be helpful in case of dysfunction of fluoroscopy during intra-operative of CRIF in a resource-limited setting.Results: The average age of patients was 39.86±14.93, the average hospital stay duration was 12 ± 8.60 days, full weight-bearing walking was around 11.64 ± 3.15 weeks and the average union time was observed to be 14.54 ± 3.36 weeks.Conclusion: This technique was successful with an efficient duration of the surgery and satisfactory results in early mobilization and fracture union time. Thus, concluding it to be a safe procedure in situations like old fracture (more than 3 weeks), pelvic injury with urethral injury, lack of traction table, and dysfunction of fluoroscopy.